GROWTH CHARACTERISTICS OF ENDOPHYTIC AND PLANT PATHOGENIC ALTERNARIA ALTERNATA AND CERATOCYSTIS SP. STRAINS - I. М. Курченко; А. К. Павличенко; О. М. Юр’єва (Mìkrobìologìâ ì Bìotehnologìâ. Мікробіологія і біотехнологія, 2013)
The aim of our investigation – a comparative study of growth characteristics and peculiarities of glucose utilization by endophytic and plant pathogenic A. alternata and Ceratocystis sp. strains. Methods. The standard methods of microbiological research were used; statistical analysis of the data was carried out. Results. The difference in specific growth rate between plant pathogenic and endophytic strains of the same species was not significant. Biomass accumulation level of endophytic Ceratocystis sp. strain was by 56.3% higher than of plant pathogenic ones, while the opposite trend observed for A. alternata strains – it was by 11.7% higher for plant pathogen than for endophyte. The opposite regularity in economic coefficient was established for Ceratocystis sp. and A. alternata strains. It was by 38.5% lower for plant pathogenic Ceratocystis sp. strain and by 40.7% – for endophytic A. alternata ones. Endophytic A. alternata and plant pathogenic Ceratocystis sp. strains characterized by high rate of glucose utilization (0.019 and 0.017 h-1 respectively). The metabolic coefficient values were lower for strains with the high economic coefficients – plant pathogenic A. alternata and endophytic Ceratocystis sp. Thus, the opposite regularities in growth characteristics of plant pathogenic and endophytic Ceratocystis sp. and A. alternata strains were established.